2019
DOI: 10.20474/jahss-5.6.4
|View full text |Cite
|
Sign up to set email alerts
|

Individual perception about the gratification of social and traditional media in Pakistan

Abstract: The current study aimed at exploring the difference between traditional and social media news and analyzed their role in grati􀅭ication of informational needs on the basis of gender and usage. Five categories of local, national, international, disaster and entertainment are selected for the survey, consisting of 1383 male and female university students from the capital of each province of Pakistan. The results are statistically analyzed by using SPSS. The 􀅭indings suggest that social media remain active to sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Additionally, using a more personalised form of language signified a more positive effect on social media credibility (Yilmaz & Johnson, 2016). Overall, it was revealed that the impact of social media credibility on both local and international political news consumption was indeed positive (Zulqarnain & Hassan, 2016).…”
Section: Perception Of Social Media Credibilitymentioning
confidence: 92%
“…Additionally, using a more personalised form of language signified a more positive effect on social media credibility (Yilmaz & Johnson, 2016). Overall, it was revealed that the impact of social media credibility on both local and international political news consumption was indeed positive (Zulqarnain & Hassan, 2016).…”
Section: Perception Of Social Media Credibilitymentioning
confidence: 92%